FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA MENGELUARKAN ZAKAT, INFAQ DAN SEDEKAH DI LAZISWAF UNIDA GONTOR - Ircham Maulaya Fadhila (Universitas Darussalam Gontor, 2021)
In recent years, people who donate, infaq and alms to the Institution of ammil zakat have increased and decreased. UNIDA Gontor students who act as muzakki as well as students who are mostly alumni of Pondok Modern Darussalam Gontor, and graduates of the boarding school should understand the science of religion, one of which is about the obligation as a Muslim to pray. This study aims to find out how the influence of ZIS Literacy (Zakat, infaq, alms), trust in institutions, attitudes, subjective norms and behavioral control on students' interest in charity, infaq and alms at Laziswaf Unida Gontor Ponorogo. Using quantitative research method and data collection technique of questionnaire method with likert scale. With a sample count of 291 out of 1172 student population living in dormitories. Analyze data using multiple linear Regression Equations using SPSS 21 and SEM AMOS 24 applications. The results of this study showed that factors of attitudes and subjective norms positively affect the interests of students berzakat, infaq and alms at Laziswaf Unida. While the factor of ZIS literacy, institutional trust, behavior control does not have a positive effect on the interests of students berzakat, infaq and alms at Laziswaf Unida.